Eye care and ocular findings at the Olympic and Paralympic Games Rio 2016. Issue 11 (2nd April 2020) - Lima, Vagner Loduca; Fernandes, Arthur Gustavo; Viana, Rodrigo Galvão; Feder, David
Abstract : Objectives: To describe the attendance and ocular profile of competitors and members of delegations who attended the Polyclinic Ophthalmology Division during the Olympic and Paralympic Games Rio 2016. Methods: The eye clinic was allocated in the purpose-built polyclinic opened for competitors and members of delegations from 24 July to 18 September 2016. All individuals who attended the service received a comprehensive ocular examination including biomicroscopy, subjective refraction and fundus evaluation. A main clinical finding was assigned for each eye by the ophthalmologist. Results: 5.6% of Olympic Games competitors and 8.9% of Paralympic Games competitors attended the Polyclinic Ophthalmology Division during the Rio Olympic and Paralympic Games. These rates compare with 2.6% and 6.5% at the London Olympic and Paralympic Games (2012). The main clinical finding was refractive error with 79.0% of the individuals receiving a glass prescription during the Olympic Games and 81.3% during the Paralympic Games. Conclusion: Our outcomes highlight the importance of the eye service at the polyclinic as it may represent the only opportunity for many individuals involved with the Olympic and Paralympic Games to receive ocular evaluation. Our description of clinic structure, delivery of service and clinical results will be useful in the organisation not only for the Olympic and Paralympic Games Tokyo 2020 but also for any other large sporting events that involves medical attention in a polyclinic format.